Post-kinematic lithospheric delamination of the Wuyi–Yunkai orogen in South China: Evidence from ca. 435 Ma high-Mg basalts - Yao, Weihua; Li, Zheng-Xiang; Li, W.; Wang, Xuan-Ce; Li, X.; Yang, J. (Elsevier BV, 2012)
Understanding the processes responsible for the intra-plate early Paleozoic Wuyi–Yunkai orogeny (> 460 Ma to 420–415 Ma) in the South China Block (SCB) is important for deducing the interactions of this block with other continents at that time, as well as the tectonic evolution of East Asia. One salient feature of the orogen is that despite the wide occurrence of syn- to late-orogenic (440 Ma to 420–415 Ma) granites in the orogen, neither syn- to late-orogenic volcanic rocks nor mafic rocks of any type have been reported. Such mafic rocks could shed clues about any mantle–crust interaction during such a major orogeny, thus help to understand the dynamics of the orogenic event. We present here, for the first time, geochronological, isotopic and geochemical data for a mafic-intermediate volcanic succession in northern Guangdong, near the edge of the metamorphic core of the orogen. The volcanic rocks unconformably overlie strongly deformed Cambro-Ordovician strata, but are in low-angle unconformable contact with overlying post-orogenic mid-Devonian strata. LA-ICP-MS and SHRIMP U–Pb dating of zircons from two andesitic and dacitic samples gives a consistent crystallization age of ca. 435 Ma, younger than the 460–445 Ma peak metamorphism of the orogeny but synchronous with the widespread late-orogenic (ca. 440–415 Ma) granitic intrusions. Nine least crustally-contaminated basaltic samples are characterized by high MgO (12.3–19.2 wt.%), Ni (214–715 ppm) and Cr (724–1107 ppm), but low TiO2 (0.6–0.8 wt.%), Al2O3 (10.2–12.8 wt.%) and Fe2O3T (total Fe as Fe2O3) (8.7–11.4 wt.%) contents. The basalts also exhibit low Nb/La ratios (0.4–0.8) and constant εNd(t) values (− 8.0 to − 8.4) with variable SiO2 (44.8–51.5 wt.%) contents, suggesting a likely sub-continental lithospheric mantle origin.These high-magnesian basalts have chemical compositions similar to their primary magma, which was estimated using geochemical modeling at SiO2 ≈ 50 wt.%, MgO ≈ 14 wt.% and FeOT ≈ 9 wt.%. The estimated potential temperature for the melts is > 1300 °C, much higher than that of a normal sub-continental lithosphere. This implies that the magma was likely generated from partial melting of lithospheric peridotite heated by hot upwelling asthenosphere. The high-magnesian andesites are interpreted as the products of differentiation and AFC processes from the same basaltic magma source, as supported by their negative zircon εHf(t) values (− 21.7 to − 6.3) and high zircon δ18O values (7.3–9.0‰). Overall, we interpret that this post-kinematic basalts, plus andesites and dacites as differentiates, resulted from a late-orogenic lithospheric delamination which led to an orogenic collapse, melting of the SCLM, and widespread late-orogenic granitic intrusions in the orogen.